Creativity as an essential aspect in medical education - Shumylo, Myroslava; Isayeva, Oksana; Khmilyar, Irena; Huziy, Ivanna; Yaremko, Halyna; Drachuk, Mariana (Creativity Studies, 2022)
The article deals with the issues of developing students’ creative skills at medical educational institutions. Intensification of students’ creative potential occurs through the formation of thinking, research and communication skills, ability to interact with information means and technologies. Second-year students of General Medicine Faculty were involved in the experiment at Danylo Halytsky Lviv National Medical University in Ukraine. Experimental and control groups included 172 students in each one. We singled out two groups: a control group – training based on the available basic course “Professional English in Medicine” and an experimental group – training based on a combination of two courses: the basic course “Professional English in Medicine” and the elective course “Special Medical Terminology”. Homogeneity of the control and experimental groups was checked using Student’s t-test. Testing 0-hypothesis showed no significant differences between samples for the reliability level 0.05 (5% probability). At the first stage of the experimental study, students’ performance was considered at the beginning of the experiment in the control and experimental groups. Students were divided into three levels: high (82–100 points), medium (64–81 points) and low (50–63 points). Certainty of differences between groups was tested using Pearson’s chi-squared test (χ2), according to which the critical value was = 5.991, and the corresponding empirical value = 0.414. Thus, any differences between the results of the control and experimental groups are random variations with a probability of less than 5%, and, therefore, the samples are homogeneous by the research indicator. Verification of reliability of the obtained results in improving the level of creativity in students was checked by Pearson’s chi-squared test (χ2), according to which the critical value equaled 5.991 and the corresponding empirical value = 6.11. Thus, any differences between the results of the control and experimental groups are with a probability of less than 5% and based on the result of introduction of an active pedagogical factor into the educational process, and, therefore, the difference between the control and experimental groups is expected for the studied indicator. To define creative abilities, we used Joy Paul Guilford’s parameters and factors for interpreting variations in creativity: sensitivity to problems; flexibility and fluency; originality; synthesis, analysis; reorganizing or redefining; complexity and evaluation; to determine verbal aspect of students’ creativity, we applied the techniques suggested by Walther Moede and Sarnoff A. Mednick. All students performed significant improvement in the ability to generate a lot of ideas; they also showed a steady increase in such forms of creativity as sensitivity to problems, flexibility and fluency. Slight increase was noticed in reorganizing or redefining, complexity and evaluation. The students’ ability to solve problems by realization of relevant analytical and synthetic operations must be taken into consideration while developing creativity and creative communication of medical students.